2008
DOI: 10.1159/000151748
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 Expression Regulation by Its Own Antisense RNA: Consequence on Tooth Development and Bone Regeneration

Abstract: Msx homeogenes play an important role in epithelial-mesenchymal interactions leading development. Msx1 is relevant for dental and craniofacial morphogenesis, as suggested by phenotypes of Msx1 mutations in human and Msx1 KO mice. During adulthood, Msx1 is still expressed in the skeleton where its role is largely unknown. Our group showed that the Msx1 gene is submitted to bidirectional transcription generating a long noncoding antisense (AS) RNA. During tooth development, Msx1 sense (S) and AS RNAs showed spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…35,36,39 Quagliata et al 40 demonstrated that lncRNA-HOTTIP positively regulates HOXA expression in HCC. The HOTTIP is located in physical contiguity with HOXA13 and directly controls the HOXA locus gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…35,36,39 Quagliata et al 40 demonstrated that lncRNA-HOTTIP positively regulates HOXA expression in HCC. The HOTTIP is located in physical contiguity with HOXA13 and directly controls the HOXA locus gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We are only beginning to understand possible mechanisms of how these ncRNAs might act on their targets, for example by impacting on sense RNA stability via sense-antisense duplex formation, targeting the sense transcript for degradation (for review see ). In recent years the function of a few lncRNAs in gene regulation has been demonstrated (Babajko et al, 2009;BlinWakkach et al, 2001;Feng et al, 2006;Lyle et al, 2000;Nagano et al, 2008;Sleutels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence points to a role for non-coding RNAs (ncRNAs) in development and disease, a field rapidly gaining importance (Babajko et al, 2009;Berdal et al, 2002;Blin-Wakkach et al, 2001;Brockdorff et al, 1991;Chen and Carmichael, 2010;Clemson et al, 1996;Costa, 2010;Eberhart et al, 2008;Faghihi and Wahlestedt, 2009;Feng et al, 2006;Ginger et al, 2006;Gupta et al, 2010;Lipovich et al, 2010;Lyle et al, 2000;Nagano et al, 2008;Qureshi et al, 2010;Rinn et al, 2007;Sana et al, 2012;St Laurent et al, 2009;Young et al, 2005). NcRNAs include microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), with an emerging class of lncRNAs that act as endogenous riboregulators of transcription factors (TFs), including lncRNAs that directly bind TF proteins to regulate them (Chen and Carmichael, 2010;Costa, 2010;Hung and Chang, 2010;Hung et al, 2011;Kino et al, 2010;Lipovich et al, 2010;Martianov et al, 2007;Redon et al, 2010;Sana et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…Given the important role of Msx1 in dental and craniofacial development, Msx1-as was shown to be and important osteogenic regulator, negatively affecting Msx1 transcript levels resulting in dose-dependent reduction of Msx1 protein levels (Babajko et al 2009, Berdal et al 2002). Moreover, the cellular location of Msx1 protein is modulated by Msx1-as and Msx1-as can abolish the inhibition of Dlx5 by Msx1.…”
Section: Osteogenesis and Osteosarcomamentioning
confidence: 99%